2022
DOI: 10.18103/mra.v10i12.3438
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Interior Lymphatic Vessel Primo Vessels in Tissue Repair

Abstract: The Primo Vascular System was discovered by Bong Han Kim in the 1960s when searching for an anatomical correlate of the acupuncture meridians used in eastern medicine. The Primo Vascular System is a systemic network of thread-like Primo-vessels with intermittent enlargements known as Primo-nodes. Primo-vessels are difficult to view under a microscope due to their small diameters (20-50 µm) and translucent appearance. Primo-vessels have a porous outer membrane that encapsulates small channels named Primo sub-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(139 reference statements)
0
0
0
Order By: Relevance
“…Moreover, the starting point of PVs is at the superior sagittal sinus and it is also symmetrically distributed along the SSS (Figure a). The PVs is a circulatory system outside of the vascular and lymphatic systems that has been found to play an important role in biological processes, including tissue regeneration, inflammation, and cancer metastasis. As indicated by the red arrows in Figure d and e, there is a pipe with a certain thickness in the periphery of the PVs, which we named PP–PVs. We found that where PP–PVs bifurcated, the PVs were also distributed in the direction of PP–PVs bifurcation and PVs did not exist until PP–PVs formed capillaries.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the starting point of PVs is at the superior sagittal sinus and it is also symmetrically distributed along the SSS (Figure a). The PVs is a circulatory system outside of the vascular and lymphatic systems that has been found to play an important role in biological processes, including tissue regeneration, inflammation, and cancer metastasis. As indicated by the red arrows in Figure d and e, there is a pipe with a certain thickness in the periphery of the PVs, which we named PP–PVs. We found that where PP–PVs bifurcated, the PVs were also distributed in the direction of PP–PVs bifurcation and PVs did not exist until PP–PVs formed capillaries.…”
Section: Resultsmentioning
confidence: 99%